Hereditary Breast-Ovarian Cancer Syndrome in Russia - Sokolenko, A.P. (A.I. Gordeyev, 2010)
Hereditary breast-ovarian cancer syndrome contributes to as much as 5–7% of breast cancer (BC) and 10–15% of ovarian cancer (OC) incidence. Mutations in the “canonical” genesBRCA1andBRCA2occur in 20–30% of affected pedigrees. In addition toBRCA1andBRCA2 mutations, germ-line lesions in theCHEK2,NBS1, andPALB2genes also contribute to familial BC clustering. The epidemiology of hereditary breast-ovarian cancer in Russia has some specific features. The impact of the “founder” effect is surprisingly remarkable: a single mutation,BRCA15382insC, accounts for the vast majority ofBRCA1defects across the country. In addition, there are two other recurrentBRCA1alleles:BRCA14153delA andBRCA1185delAG. BesidesBRCA1, in Russia breast cancer is often caused by germ-line alterations in theCHEK2andNBS1genes. In contrast toBRCA1andBRCA2, theCHEK2andNBS1heterozygosity does not significantly increase the OC risk. Several Russian breast cancer clinics recently started to investigate the efficacy of cisplatin in the therapy ofBRCA1-related cancers; initial results show a unique sensitivity ofBRCA1-associated tumours to this compound.